Prohibition of Marriage Between Sundanese and Javanese Tribes - Rahmadiani, Adisti Putri; Hasuna, Asma Nadia; Ni’ma Hilya, Moh Zacky; Rahmani, Salsabila Putri; Komariah, Siti (JUPE : Jurnal Pendidikan Mandala, 2024)
Indonesia is a country full of social and cultural diversity, with each element having a different historical background. One of the stories that became the forerunner of the tradition of prohibiting marriage between Sundanese and Javanese people in the year was the Bubat War between the Majapahit Kingdom and the Sunda Kingdom. The purpose of this research is to analyze the factors behind this prohibition and understand the family's goals in carrying out this tradition. The methodology used in this research is qualitative, by collecting data through literature studies and literature reviews The findings indicate that the prohibition of marriage is influenced by the history of the Bubat War and stereotypes regarding caste differences, where the Javanese are perceived to have a higher status than the Sundanese. The purpose of this prohibition is to prevent the belief that marriages between the two ethnic groups will not last long, as well as to avoid financial issues and maintain household harmony.